Colors for letters in Chinese and English bilinguals - Tan, Vincent Wei Jun (2019)
Grapheme-color association, also known as letter-color association, has been reported to be present in individuals without synesthesia and is related to linguistic priming of initial letters of various color terms. In this study, the author conducted a repeated measures study to investigate whether individuals have an implicit grapheme-color association through a) whether Chinese-English bilinguals are non-random in their selection of colors for Latin letters of the English alphabet and b) whether language proficiency influences their selection of colors. Participants were presented all 26 Latin letters of the English alphabet, one at a time, and tasked to match these letters of the English alphabet to a color that they think go best with the presented letter. The author used a reproduced chromatic array from the World Color Survey (1969) for participants to select their match letters to colors. Results revealed that participants’ choices were significantly non-random, but language proficiency was not found to be significantly correlated to participants’ choice of colors. The findings partially supported previous research findings and limitations and suggestions for future studies are discussed with regards to grapheme-color associations in Mandarin Chinese.